2000
DOI: 10.1097/00002030-200012220-00007
|View full text |Cite
|
Sign up to set email alerts
|

Virological and immunological effects of treatment interruptions in HIV-1 infected patients with treatment failure

Abstract: Changes in surrogate markers suggest that treatment provided benefit in spite of virological failure and resistant virus. Although patients with a shift to wildtype virus responded better in the short term to treatment re-initiation, the long-term effects are not known and the risk of immune deterioration needs to be carefully considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
115
7

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(126 citation statements)
references
References 21 publications
4
115
7
Order By: Relevance
“…After treatment interruption, a higher rate of viral replication and a rapid decline in CD4 ϩ cells was observed in this study, in concordance with previous reports (10,12,16,26,45,59). In order to determine if these changes in viral replication and cytopathogenicity were caused by the emergence of variants with a syncytium-inducing/CXCR4 phenotype, the coreceptor usage by HIV-1 was inferred from V3 loop sequences.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…After treatment interruption, a higher rate of viral replication and a rapid decline in CD4 ϩ cells was observed in this study, in concordance with previous reports (10,12,16,26,45,59). In order to determine if these changes in viral replication and cytopathogenicity were caused by the emergence of variants with a syncytium-inducing/CXCR4 phenotype, the coreceptor usage by HIV-1 was inferred from V3 loop sequences.…”
Section: Discussionsupporting
confidence: 90%
“…It was previously reported that not all the patients with treatment failure undergoing STI experienced a reversal in their drug-resistance-associated genotype (10,12,16,26,45,59). Elucidating the factors that could predict which patients would revert from their drug-resistant genotype to a drug- sensitive one after STI would be of great use for the physicians managing patients with ARV treatment failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present findings evoke an argument regarding continuation of incomplete HAART. When HAART results in incomplete suppression of virus replication due to emergence of variants resistant to the available drugs, some clinical trials currently recommend continuation of therapy, because any interruption could result in increased plasma viral load and low CD4 cell counts (3,9,19). In general, it is believed that continuation of HAART under such circumstances can still produce some clinical benefits because of the reduced replication capacity of the PI-resistant virus (9).…”
Section: Table 3 Amino Acid Substitutions In Gag P17mentioning
confidence: 99%